SOCIAL MEDIA AND CONSUMER BUYING DECISIONS IN TOURISM: A CASE OF AMRITSAR CITY (International Journal of Food and Nutritional Sciences, 2022)
In the modern era, the place of information and communication technology (ICT) is wider in scope. Social media is an online platform where one can get access to every minute detail. Social media and tourism share a relationship in terms of traveling decisions as it influences the consumer preferences. It is a network to share ideas, information, thoughts and experiences through an online mode. Furthermore, it facilitates the consumer to interact with travel professionals and learn about the facts of this sector. There are many features of tourism products like perishability, inseparability, non- ownership, intangibility and dominant role of suppliers. Hence, it is quite clumsy for consumers to choose trustworthy components. In this picture, the only thing that could aid the tourist to get evidence is through social media channels. Social media act as a supporter, guide and consultant of this industry. Additionally, this platform is not only about sharing good memories, but many consumers share the bad experiences too. Moreover, there are countless tourism players who have been using this media to boost the sales and profits.